Indian Ocean histories
1 online resource
Keywords: "Michael Naylor Pearson's work falls under the genre of global or world history and has tremendous impact on the study of the Indian Ocean world. He brought together different disciplines, and emphasized on the holistic view of the worlds of water. This book will serve as a guide and as a reader for Indian Ocean studies. It brings together scholars from different disciplines across the world (all of whom have been influenced by Michael Pearson's work) and points out several ways of writing the Indian Ocean history. The book discusses the changing nature of Indian Ocean history along with state and capital, regional identities, maritime networking, Islamic conversions, south Asian immigrants, Bay of Bengal linkages, East India Company, Indian seamen, the issues of colonial copyright, customs, excise and port cities etc. among many themes to give a comprehensive understanding of the study of Indian Ocean. With maritime history gaining prominence, this volume will be useful for scholars and researchers of history, modern history, medieval history, Indian history, colonial history and world history"--